The Effectiveness of Movement-Based Psychotherapy on Couple Intimacy - Mokarami, Zakiye; Soleimanian, Aliakbar; Rahimi Pordanjani, Tayebe (Applied Family Therapy Journal (AFTJ), 2024)
Objective:  The aim of the present study was to examine the effectiveness of movement-based psychotherapy on couple intimacy.Method: The research employed a single-case experimental design with multiple baselines. The statistical population consisted of all couples who visited counseling centers in Bojnord City in 2021. From this population, three couples who met the inclusion criteria were selected through purposive criterion-based sampling. Measurements were conducted using the validated Couple Intimacy Needs Questionnaire by Bagarozzi (2012). Participants were assessed over three baseline sessions, 12 intervention sessions, and three follow-up sessions. Data analysis was performed using visual analysis at both within-case and between-case levels.Findings: Results indicated an increase in intimacy for all participants. The graph lines demonstrated an upward trend in data changes during the intervention phase, with a high percentage of Nonoverlapping Data (PND) and a low percentage of Overlapping Data (POD). Additionally, in the follow-up phase, intimacy continued to increase for four individuals (two couples) and remained within the intervention range for two individuals (one couple), indicating that movement-based psychotherapy was effective in enhancing intimacy between couples.Conclusion: The results showed that movement-based psychotherapy, by utilizing the body as a tool to access the unconscious and applying techniques such as mirroring and fostering an understanding of each individual’s needs and emotions in their partner, increased awareness and recognition of personal and partner needs, thereby enhancing intimacy between couples. It is recommended that this method be implemented in therapeutic and counseling centers to enrich marital relationships.